POTENTIAL FOOD ITEMS FOR THE ANDEAN FLAMINGO (PHOENICOPARRUS ANDINUS, (PHILIPPI, 1854)) IN TWO TYPES OF AQUATIC HABITATS FROM THE PARINACOCHAS LAKE, AYACUCHO, PERU - Ortiz, Enver (2020)
The presence of a certain species in a place obeys several factors; one of them is the available food resources. In this work, we report the main and potential food items for the Andean Flamingo Phoenicoparrus andinus (Philippi, 1854) would have access to at the end of the winter season in the Parinacochas Lake, Ayacucho in Peru. 21 types of microalgae were found in water associated with shallow puddles and 15 in free surface water: 17 were diatoms (Bacillariophyta), two dinofl agellates (Dinophyceae), and two cyanobacteria (Cyanophyceae) with potential contributions to the diet of 80.96%, 9.52%, and 9.52%, respectively. Surirella sp. was present in all the water samples, and it was also the most abundant, followed by the oscillatoriales that were found in 90% of the samples. Between the two types of habitats, there were more than 12 shared species were registered (60% of similarity) and concerning the distribution of the microalgae in both habitats, the conformation of two undiff erentiated groups was observed, this was due to several factors such as the salinity to which they were exposed and the proximity to hot springs, which could infl uence the distribution and therefore availability and accessibility of microalgae as potential food items for the Andean Flamingo in the northernmost site of its distribution in South America.